Pengaruh Islamic Branding, Product Ingredients dan Promosi Terhadap Minat Beli Produk PT. HNI HPAI Kota Malang - Bella Zakila; Siti Asiyah; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Indonesia is a country with a Muslim majority population which tends to assume that all products in circulation are halal products. One of the difficulties faced by Muslim consumers in Indonesia is finding herbal and halal medicinal products. In addition, this is supported by Muslim consumers who are currently increasingly looking for herbal and halal medicines. This study aims to determine the effect of Islamic branding, product ingredients and promotion on the intention to buy HNI-HPAI products in Malang City, the population that is the object of this research is Consumers of HNI-HPAI Products at Business Center I HPAI Malang City. The sample used was 89 people. Sampling in this study used the saturated sample method. The analytical method used in this study is a multiple regression analysis method with the SPSS19 application. The results of the research based on partial hypothesis testing (t test) show that Islamic branding, product ingredients and promotions partially have a significant effect on purchase intention. The results of the F test of Islamic branding, product ingredients and promotion together have a positive and significant effect on purchase intention. This can be seen in the Fcount value of 52.146 > Ftable 2.71 and a significant value of 0.001 <0.05. The test results for the coefficient of determination (R2) obtained an Rsquare of 0.636. This shows that the dependent variable buying interest can be explained by the independent variables Islamic branding, product ingredients and promotions 63.6% while 36.4% is explained by other factors outside the variables studied. Keywords:Islamic Branding, Product Ingredients, Promotion, Buying Interest, HNI HPAI.